Optimal bus service operation considering bus bunching elimination, bus contracting and collaborative freight transport - Zhou, Chang (Nanyang Technological University, 2023)
Public transport services are important assets to any major city. They play a vital role in improving urban mobility, reducing car dependency, and mitigating traffic congestion. It is ideal if public transport services are financially sustainable with expedient service quality. To achieve this goal, the key lies in how the full capacity of the existing public transport system can be exploited through optimal decisions on planning and operation. This thesis uses public bus services as an example to elaborate on how to achieve a more sustainable public transit system via determining the best decisions in three dimensions: self-operation, i.e., how to design the optimal bus service operation strategies at the operational level; outsourcing, i.e., how to determine the best bus contracting policy in the strategic planning level, and sharing, i.e., how to introduce collaborative freight transport service into existing bus transit system in the tactic level. Most specifically, we select one topic for each dimension, and these topics include bus bunching mitigation, bus routes packaging and allocation to private bus service operators, and collaborative freight transport.